Color preference of the Malay population in the design of a virtual environment - Zahari, Taha; Soewardi, Hartomo; Siti Zawiah, Md Dawal (2012)
One of factors contributing to the incidence of cyber sickness in a virtual environment is color. This paper describes an investigation of the color preference in a virtual environment of the Malay population. A survey was conducted on the color preference of the , virtual static object and motion object. 64 subjects, (N = 34 male and N = 30 female, age between 17 to 50 years old), participated in the survey. Participants were asked to choose their 10 favorite single color for the virtual background color, virtual static and motion object color. Two tailed Z-test was conducted to test the difference between male and female color preference. The results show that red and medium slate blue colors are the most preferred colors for the virtual background by both, male and female. Red, blue, and deep pink colors are the most preferred colors for the virtual static object for both, male and female. And red and black colors are the most preferred colors by both, male and female, for virtual motion object.